2019
DOI: 10.18502/npt.v6i2.912
|View full text |Cite
|
Sign up to set email alerts
|

Study of knowledge and attitude of nurses in Sanandaj city toward organ donation

Abstract: Background & Aim: Nowadays, organ transplantation is the final treatment for the patients with end-stage organ dysfunction. Considering the importance of the organ donation and the important role of nurses in increasing the number of organ donations, the present study aimed to determine the knowledge and attitudes of nurses in Sanandaj hospitals toward organ donation. Materials & Methods: This study was descriptive-analytic (cross-sectional). 250 nurses working in hospitals in Sanandaj city were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…The present study illustrated that the most used source of information regarding organ donation and transplantation was TV. The results of several studies done in Iran and other foreign studies were consistent to this study and in all of them TV was found as the main source of information ( 17 , 19 , 27 34 ). The results of the study carried out by Manzari et al among families with brain dead patient, pointed to the effective role of TV in decision-making of family regard donating their family member organs ( 35 ).…”
Section: Discussionsupporting
confidence: 91%
“…The present study illustrated that the most used source of information regarding organ donation and transplantation was TV. The results of several studies done in Iran and other foreign studies were consistent to this study and in all of them TV was found as the main source of information ( 17 , 19 , 27 34 ). The results of the study carried out by Manzari et al among families with brain dead patient, pointed to the effective role of TV in decision-making of family regard donating their family member organs ( 35 ).…”
Section: Discussionsupporting
confidence: 91%
“…The lowest score is 18 and the highest score is 72. Content validity and the reliability of the knowledge and attitude questionnaire have been confirmed by Valiee et al in 2019 (15). In this study, the content validity of the questionnaires was confirmed by 15 nursing professors of Fasa University of Medical Sciences.…”
Section: Methodssupporting
confidence: 74%
“…In this regard, the results of studies conducted by Naçar et al (2015) in Turkey, Khalid et al (2019) in Pakistan, Poreddi et al (2016) in India and Huern et al (2016) in Malaysia showed that nurses' knowledge of organ donation was at low level and educational interventions were needed in this area (11)(12)(13)(14). Nursing staff can play an important role in the organ donation process and the most studies conducted in Iran on nurses' knowledge and attitudes about brain death and organ donation are descriptive and limited interventional studies have been conducted in this area, and these interventional studies have used only lecture form of education and less modern educational method of clinical scenariobased method leading to active and deep learning has been used (15)(16)(17). Hence, the present study was conducted to evaluate the effect of clinical scenario-based educational workshop and re-thinking on the knowledge and attitude of head nurses and clinical supervisors in the area of organ donation in Fasa Hospital in southwestern of Iran in 2019 (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Recently, research has focused on the important role of nurses in brain death and the organ donation process. [ 3 ] Nurses are important professionals in this area because they measure the vital signs of patients, and maintain hemodynamic stability so that donor organs remain viable. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] In addition, results of previous studies have shown that nurses play several roles in this regard such as identifying potential organ donors, effectively following-up on the needs of brain dead patients' families, educating the public, and care of possible organ donors. [ 3 6 8 ] The latter may be extremely important to the success of organ donation. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%